EU enlargements, Brexit and value-added trade: A structural gravity approach - Jan Hagemejer; Jakub Mućk (PLoS ONE, 2025)
We revisit the topic of trade effects of past EU enlargements. We employ a structural gravity model to flows of domestic value added embedded in international trade and absorbed in the foreign final demand for the period of 1995–2018. Our model takes into account the current state of the art in estimation of gravity models: PPML estimation and multi-dimensional fixed effects. We base our estimations on the TiVA dataset and provide aggregate and sectoral estimates. Our results show stable estimates of EU enlargement on value-added trade of the order of 13.9% depending on the specification. These results are also robust to a choice of an alternative dataset (WIOD database). The advantage of our approach is the direct calculation of the trade impact on the GDP level. Based on these estimates we also provide quantitative insights into the effects of Brexit which varies depending on the country-specific exposure to the value added trade with the UK.